Lymphomas and Kaposi’s Sarcoma in South Ethiopia: results from a cancer registry 1963 – 1986 - Lindtjorn, Bernt (My University, 2019)
The pattern of Non-Hodgkin's lymphoma and aggressive Kaposi's sarcoma is known to have changed in some countries as the prevalence of the acquired immunodeficiency syndrome increases. A retrospective analysis of histologically verified cancers in southern Ethiopia during the period 1963-86 did not demonstrate any change in the pattern of aggressive Kaposi's sarcoma nor of Non-Hodgkin lymphomas, suggesting that the HIV epidemic did not start before the mid-1980s.
Keywords: Ethiopia; Kaposis sarcoma; Lymphoma; Trend